The tea ceremony and women's empowerment in modern Japan : bodies re-presenting the past - Katō, Etsuko, 1965- (Anthropology of Asia series (Richmond, England), 2004)
"The subject of the tea ceremony is well researched both in and outside of Japan, but the women who practice it are hardly ever discussed. The Tea Ceremony and Women's Empowerment in Modern Japan rectifies this by discussing the meaning of the Japanese tea ceremony for women practitioners in Japan from World War II to the present day. It examines how lay tea ceremony practitioners have been transforming this cultural activity while being, in turn, transformed by it." "Drawing on Foucault's concept of discipline and focusing primarily on the body, this book illuminates how women tea ceremony practitioners have empowered themselves through a unique way of using their bodies."